The Adoption and Use of Digital Literacy Programs in Selected Tertiary Institutions of Tanzania - Bulugu, Paskazia Patric; Nkebukwa, Leontine (Indonesian Journal of Social Research (IJSR), 2024)
The purpose of this research is to assess the adoption and use of digital literacy in Tanzanian tertiary institution libraries, focusing on the current state of digital literacy acceptance, the practical implementation, and the obstacles associated with embracing and implementing digital literacy in library settings.The study employed a mixed-method approach, simultaneously using qualitative and quantitative methods. Thus, the primary data were collected through interviews with key informants, including librarians and ICT experts. The quantitative data were gathered through a semi-structured questionnaire. Subsequently, thematic analysis and statistical techniques were employed to analyze the collected data. The findings discovered that a majority had embraced and implemented digital literacy, though numerous challenges were reported. These challenges ranged from technophobia, lack of guidance for digital literacy programs, inadequate power supply, and limitations of internet connectivity. Improving digital literacy in libraries contributes to comprehensive educational development and enhanced access to digital resources to fill knowledge gaps and foster comprehensive social learning